2015
DOI: 10.2217/epi.15.13
|View full text |Cite|
|
Sign up to set email alerts
|

Introducing Enteral Feeding Induces Intestinal Subclinical Inflammation and Respective Chromatin Changes in Preterm Pigs

Abstract: Enteral feeding, particular with formula, induces subclinical inflammation in the premature intestine and more open chromatin structure in key inflammatory genes. This may increase the susceptibility for necrotizing enterocolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…CXCL10 encodes a chemokine ligand CXCL10 for the CXCR3 receptor leading to immune stimulation, consistent with increased expression in the colon after dextran sulfate-induced ulceration in mice (61). We observed increased IF-related TLR2 expression (gram-positive G320 DIET AND EARLY FEEDING FOR PRETERM NEONATES bacterial receptor), consistent with some rat NEC studies (36) but limited effects on expression of the gram negative bacterial receptor, TLR4, consistent with our earlier studies in preterm pigs (4,48,63,69). A subset of samples from the middle intestine was used to investigate intestinal inflammation and immunity genes in more detail, including their chromatin structures (69).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CXCL10 encodes a chemokine ligand CXCL10 for the CXCR3 receptor leading to immune stimulation, consistent with increased expression in the colon after dextran sulfate-induced ulceration in mice (61). We observed increased IF-related TLR2 expression (gram-positive G320 DIET AND EARLY FEEDING FOR PRETERM NEONATES bacterial receptor), consistent with some rat NEC studies (36) but limited effects on expression of the gram negative bacterial receptor, TLR4, consistent with our earlier studies in preterm pigs (4,48,63,69). A subset of samples from the middle intestine was used to investigate intestinal inflammation and immunity genes in more detail, including their chromatin structures (69).…”
Section: Discussionsupporting
confidence: 91%
“…After feeding preterm pigs for 5 days, NEC lesions and a series of gut structural, functional, immunological, and microbiological parameters were measured. Some of the preterm pigs in this study were previously used to show how the first enteral feeding increases physical activity (11) and a series of intestinal inflammatory and pattern recognition receptor genes with corresponding changes in chromatin structures (69).…”
mentioning
confidence: 99%
“…Our results show that the developmental expression of these enzymes is relatively independent of environmental factors, such as diet (which was the same for preterm and term pigs), and that intrinsic mechanisms related to ontogenetic age and genetic control could be more important. We recently documented that both preterm birth and enteral food introduction induce epigenetic effects on some immune-related genes in the immature pig intestine (19,53). It will be important to know whether preterm birth also induces epigenetic modifications to the sucrase-isomaltase and maltaseglucoamylase genes because this may help to explain why their corresponding enzyme activities were affected more long term whereas other gene functions tended to adapt more rapidly after preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…On day 5, the PN was discontinued and all piglets were given increasing amounts of raw bovine milk (64 -150 ml·kg Ϫ1 ·day Ϫ1 ) to day 9 and subsequently transferred to reconstituted whole milk powder at 150 -200 ml·kg Ϫ1 ·day Ϫ1 (Arla Foods Ingredients, Viby, Denmark) until day 26. The dosing strategies for both TPN and enteral feeding are comparable with the feeding advancement rates used for moderately preterm infants (4,13,17,25,53). See Fig.…”
Section: Animals and Nutritionmentioning
confidence: 92%
“…Human milk and other enterally given products change gene expression especially with methylation [38]. In studies performed in preterm infants and pig models, it was shown that proinflamatory genes became upregulated by enteral feeding [39] [40]. Also important risk factors in NEC pathogenesis such as intestinal microflora and intestinal splanhcnic perfusion has mutual interaction with enteral feeding type [41] [42].…”
Section: Enteral Feedingmentioning
confidence: 99%